Wage differential between statutory and CLT public employees - Mancha, André Luiz Pereira (2018)
Since 1998 in the Public Administration there are statutory workers ('estatutários') and others hired by the CLT labor regime ('celetistas'). Thisfact occurs due the Constitutional Amendment number 19 , formulated that year, which has changed the article 39 of Brazilian Constitution. It allowed public entities to hire employees under CLT legislation. This situation lasted until 2007 when the Supreme Court of Brazil suspended such modification and so the original understanding of the Constitution was reestablished. This work intends to evaluate the wage differential between statutory and CLT employees by means of an econometric approach. Using a fixed effectsregression we have analyzed the impact of the labor regime upon public workers wages and using the Oaxaca-Blinder decomposition we quantified how much of such differential is due the labor regime and how much is due to the individual characteristics (education, tenure and others). There are evidences that CLT workers have in average wages R$ 310.00 lower than statutory. Controlling by occupation we also see a negative prize to CLT worker to all groups except by the High Skilled Workers that have a salary R$ 95.98 higher than the Statutory. Low Skilled Workers show the smallest differential (R$ 12.20) followed by Teachers and Researchers (R$ 85.27) and Technicians (R$ 97.11). The Oaxaca-Blinder decomposition shows that the largest part is not explained by endowments differences. The spending with wages and benefits to public employees is one of the main debates in the current scenario of fiscal adjustment facing the relevant increase of Public Debt in the last years. The Brazilian society has a perception that the Government has an excessive amount of workers and furthermore these onesreceive higher wages without a reasonable explanation when compared to similar occupations in private companies. At the end of 2017 the Brazilian Government presented an action plan to reduce the spending with wages and benefits of public employees. Among the proposals there were a decrease in the initial salary of public service and an increase in the public pension plan contribution.